2021
DOI: 10.1108/jfc-05-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Fraudulent financial reporting: an application of fraud diamond to Toshiba’s accounting scandal

Abstract: Purpose The purpose of this paper is to examine Toshiba’s fraudulent financial reporting in relation to the fraud diamond (pressure, opportunity, rationalisation and capability). Design/methodology/approach A quantitative empirical research, analysing secondary data from Toshiba’s published annual reports before restatement, from 2008–2014 has been used. A simultaneous equations approach was used to test the hypothesis. Excel software was used to analyse secondary data and to carry out correlation analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 84 publications
0
12
0
3
Order By: Relevance
“…Financial Target and Financial Shenanigans. High financial targets have the potential of causing management to engage in financial shenanigans in order to demonstrate good corporate performance (Fitri et al, 2019;Devi et al, 2021;Demetriades and Owusu-Agyei, 2022). Consequently, the higher the company's financial target, the more pressure management will face, forcing management to commit fraud (Ramírez-Orellana et al, 2017).…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…Financial Target and Financial Shenanigans. High financial targets have the potential of causing management to engage in financial shenanigans in order to demonstrate good corporate performance (Fitri et al, 2019;Devi et al, 2021;Demetriades and Owusu-Agyei, 2022). Consequently, the higher the company's financial target, the more pressure management will face, forcing management to commit fraud (Ramírez-Orellana et al, 2017).…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…The change of directors also occurred allegedly due to a mismatch with the directors who were not in line with committing fraud (Imtikhani & Sukirman, 2021). Directors who have knowledge of fraud are removed to weaken internal control operations and avoid detection (Demetriades & Owusu-Agyei, 2021). According to agency theory, management in carrying out its role as an agent is equipped with capabilities that can be a door for committing fraud that has a negative impact on the company (Devi, Widanaputra, Budiasih, & Rasmini, 2021).…”
Section: Image 1 the Fraud Hexagonmentioning
confidence: 99%
“…In the director's change capability, it affects the FSF (Aviantara, 2021;Xu, Lin, & Chen, 2018;Yulistyawati, Suardikha, & Sudana, 2019;Devi, Widanaputra, Budiasih, & Rasmini, 2021) while some research results were found to have no significant effect (Handoko & Tandean, 2021;Imtikhani & Sukirman, 2021;Demetriades & Owusu-Agyei, 2021;Vivianita & Indudewi, 2018). On the opportunity, Demetriades & Owusu-Agyei (2021), Devi, Widanaputra, Budiasih, & Rasmini (2021), and Imtikhani & Sukirman (2021) found that monitoring effectiveness affected FSF, while Handoko & Tandean (2021) did not. On rationalization, Auditor changes were found to affect the FSF (Imtikhani & Sukirman, 2021) but also had no effect on the research by Handoko & Tandean (2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations